Borut Belec's Contribution to the Study of Peripheral (Marginal) Areas of Slovenia - Lorber, Lučka (Journal for Geography, 2015)
The Slovenian geographer and professor emeritus Borut Belec made his greatest scientific contribution in the second half of the 20th century, when Agrarian Geography was characterized by a decline in its theory and by the lack of interest of the leading Slovenian geographers. Borut Belec studied changes in land use of peripheral and border areas of the North-Eastern Slovenia. His active participation in research projects and his early entry into the international area resulted in the upgrade of his research work with the study of distant locations from the perspective of the humanistic components of the Agrarian and Regional Geography. Borut Belec has enriched the Slovenian Agrarian Geography above all by studying land use in relation to the development of viticulture over long periods of time. At the local level, he studied changes in land use and acknowledged their influence on demographic changes, on workforce commuting, and on the marginality and transport accessibility of peripheral areas. He was the pioneer of the scientific approach to the study of the peripherality and marginality in Slovenia. His scientific findings were published in renowned journals and presented at international geographical congresses. With the integration of graduates into his scientific work, he was able to transmit his knowledge to new generations of young geographers.
Keywords: Borut Belec; geographer; rural geography; peripherality; marginality; border areas